The Role of Competence, Independence, Professional Commitment, and Professional Oversight on Audit Quality and Reputable Public Accounting Firm Model in Indonesia - Yulia Tri Kusumawati; Abdul Halim (Politeknik Siber Cerdika Internasional, 2026)
Background: The auditing profession continues to face a credibility crisis due to recurring corporate scandals that undermine public trust in audit quality and Public Accounting Firm (PAF) reputation. Previous studies examining the effects of auditor competence and independence have reported inconsistent findings, indicating the need for a more comprehensive model that incorporates moderating and mediating variables. Objective: This study aims to develop a reputable PAF model in Indonesia by examining the effects of competence and independence on audit quality and PAF reputation, with professional commitment and professional oversight serving as moderating variables and audit quality serving as a mediating variable. Methods: A quantitative explanatory survey was conducted involving 1,432 active Public Accountants in Indonesia. Using random sampling, 312 respondents were selected, of whom 289 provided valid responses. Data were collected through structured questionnaires and analyzed using Smart Partial Least Squares (SmartPLS), including measurement model evaluation and moderation–mediation analysis. Results: Competence and independence significantly enhance audit quality and PAF reputation. Professional commitment and professional oversight strengthen the effects of competence and independence on audit quality, while audit quality significantly mediates the relationship between these factors and PAF reputation. These findings support an integrated model that links individual, professional, and organizational factors. Conclusion: A reputable PAF is established through the integration of competence, independence, professional commitment, professional oversight, and audit quality. This model provides practical guidance for strengthening audit credibility, enhancing competitive advantage, increasing stakeholder trust, and supporting the long-term sustainability of Public Accounting Firms in Indonesia.